Magnitude of the White-Coat Effect in the Community Pharmacy Setting: The MEPAFAR Study (2011)
ABSTRACT: Background There is little information regarding the community pharmacy blood pressure (CPBP) measurement method and their differences with home (HBP) or ambulatory BP (ABP). The aim of this study was to measure such differences and their variation over successive visits. Method Cross-sectional study carried out in eight pharmacies in Gran Canaria (Spain). The study included 169 treated hypertensive patients. BP was measured at the pharmacy (four visits), at HBP (4 days) and 24-h ABP monitoring. We defined pharmacy white-coat effect (PWCE) as differences between CPBP and HBP (home PWCE) or daytime ABP (ambulatory PWCE). Results The overall (pooled values for all visits) ambulatory PWCE was not significantly different from zero for systolic BP (SBP) (−0.4mmHg (95% confidence interval (CI): −1.8 to 1.1)), but greater than zero for diastolic BP (DBP) (3.4mmHg (95% CI: 2.3 to 4.6)). The overall home PWCE was not significantly different from zero, both for SBP (1.2mmHg (95% CI: −0.1 to 2.6)) and DBP (0.1mmHg (95% CI: −0.7 to 1.0)). The ambulatory and home PWCE on the first visit were greater than zero (P < 0.001) (SBP/DBP): 3.5/4.8 and 1.9/1.5mmHg, respectively; but showed important reductions at the second visit and became not significantly different from zero, except the ambulatory PWCE in DBP, which persisted until the last visit. Conclusión The trend in the PWCE decreased over the successive visits to the pharmacy. Only the ambulatory PWCE in DBP proved to be statistically greater than zero after the second visit. Repeated CPBP measurements could be a useful alternative to assess the response to antihypertensive treatment.